Dietary guidance for patients with depressive disorder: A retrospective study focusing on factors associated with discontinuation - Kunugi, Hiroshi; Kasahara, Kohei; Miyamoto, Kayoko; Segawa, Kazuhiko (New diet therapy, 2024)
Accumulating evidence has suggested the importance of nutritional approaches in the treatment of depressive disorder. In this study, we tried to identify main nutritional conditions targeted for the guidance of depressed patients and factors associated with continuation/discontinuation of the guidance for 6 months. We retrospectively reviewed medical charts of 43 patients with depressive disorder who underwent nutritional guidance by registered dietitians at the National Center of Neurology and Psychiatry Hospital. As a result, most of the requested diseases in the guidance of depressed patients were conditions related to metabolic syndrome. Continuation of the guidance for 6 months was related to a longer history of depression, taking antidepressants, a history of receiving guidance in the past, higher BMI, and type 2 diabetes mellitus. The discontinuation group had a higher rate of missed meals. There was no clear change in BMI of the guidance-continuation group; however, some obese patients showed a substantial reduction of BMI. These results warrant further investigations for the nutrition guidance for depressed patients.